2005
DOI: 10.1111/j.1365-313x.2005.02405.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of WXP1, a putative Medicago truncatula AP2 domain‐containing transcription factor gene, increases cuticular wax accumulation and enhances drought tolerance in transgenic alfalfa (Medicago sativa)

Abstract: SummaryThe identification of leaf wax genes involved in stress tolerance is expected to have great potential for crop improvement. Here we report the characterization of a novel AP2 domain-containing putative transcription factor gene from the model legume Medicago truncatula. The gene, designated WXP1, is able to activate wax production and confer drought tolerance in alfalfa (Medicago sativa), the most important forage legume species in the world and a close relative of M. truncatula. The predicted protein o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
272
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 382 publications
(288 citation statements)
references
References 71 publications
10
272
1
5
Order By: Relevance
“…V. faba flower wax was characterized by high levels of C 22 alcohol (Griffiths et al, 1999), in contrast to either C 26 or C 30 alcohols in leaf waxes of the closely related Fabaceae spp. Phaseolus vulgaris (Steinmüller and Tevini, 1985), Medicago truncatula (Zhang et al, 2005), and Pisum sativum (Gniwotta et al, 2005; the composition of V. faba leaf wax has not been reported yet). Arabidopsis flower wax is dominated by C 29 alkane (Shi et al, 2011), shorter than the prevalent C 31 homolog in leaves (Jenks et al, 1995) but similar to inflorescence stems and siliques (Todd et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…V. faba flower wax was characterized by high levels of C 22 alcohol (Griffiths et al, 1999), in contrast to either C 26 or C 30 alcohols in leaf waxes of the closely related Fabaceae spp. Phaseolus vulgaris (Steinmüller and Tevini, 1985), Medicago truncatula (Zhang et al, 2005), and Pisum sativum (Gniwotta et al, 2005; the composition of V. faba leaf wax has not been reported yet). Arabidopsis flower wax is dominated by C 29 alkane (Shi et al, 2011), shorter than the prevalent C 31 homolog in leaves (Jenks et al, 1995) but similar to inflorescence stems and siliques (Todd et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overexpression of AP2 domaincontaining transcription factors (Aharoni et al, 2004;Broun et al, 2004;Zhang et al, 2005) has increased cuticular wax load, but no novel components were reported. This study shows that, with the appropriate biosynthetic gene, it is possible to produce novel cuticular wax components that are transported to the surface.…”
Section: Biotechnology Of Plant Cuticlesmentioning
confidence: 99%
“…To this end, gene candidates for drought tolerance are now being expressed in lucerne. One of these is the WXP1 transgene responsible for production of cuticular wax and where 'proof of concept' experiments demonstrated that insertion of WXP1 increased lucerne's ability to be productive, and even recover more quickly, after periods of limited water (Zhang et al 2005).…”
Section: Drought Tolerancementioning
confidence: 99%